Financial Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
Prior research supports the view that South African Small, Medium and Micro Enterprises (SMMEs) add significant socio-economic value to the national economy. Unfortunately, these business entities’ sustainability leaves much to be desired as they are reported to be among the worst in the world - an estimated 80% of South African SMMEs fail after being in existence for only three years. Although the sustainability of these business entities is believed to be adversely affected by an array of risks which realise (stemming from a harsh economic environment), it is imperative that South African SMMEs make use of sound internal control initiatives to mitigate such risks. According to scholarly literature, it appears that South African SMMEs make use of customised internal control initiatives which are often viewed as inadequate and/or ineffective which, in turn, do not properly mitigate risks. This may result in the sustainability of these business entities to be adversely affected. In order to shed light on the preceding phenomenon, for this study, a literature review was conducted to investigate the theoretical relationship that exists among internal control initiatives, occupational fraud risk, and SMME sustainability, in a South African context.